Ճարտարապետական ժառանգության պահպանությունը արդի քաղաքաշինական զարգացումներում - Կիրակոսյան, Լյուբա (ԱրՊՀ հրատ․)
Arcհitecture has been the pride of the countries in all times. Especially for us, for Armenians, it is more important direction, because we have a serious architectural heritage, the protection of which is the responsibility of all generations. Modern urban processes in Armenia have such deve-lopments that very often historical-architectural environment is spoiled, but it is known that the basis of the national architecture is the philosophical unity of tradition and innovation. Only such an architectural direction, which carries this philosophy will give Armenian cities, especially Yerevan, the opportunity to restore open-hearted and pink feature, which it used to have instead of eclectic neutrality, which dominates nowadays. But this isn’t typical for Stepanakert, because in the capital of Kharabakh modern buil-dings are in harmony with old ones and don’t spoil the historical-arci-techural invironment.
Keywords: Ճարտարապետություն; Արցախ